2018
DOI: 10.1123/jsr.2016-0197
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Anterior Knee Displacement During Squatting on Patellofemoral Joint Stress

Abstract: Findings provide some general support for minimizing forward knee translation during squats for patients that may have patellofemoral pain syndrome.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
21
1
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(26 citation statements)
references
References 42 publications
1
21
1
1
Order By: Relevance
“…For both types of verbal instruction (FoAin and FoAex), participants demonstrated a medium or large reduction in PFJFs and PFJS compared with baseline (based on the effect size statistic). These results supplement earlier findings, which indicated that knee loading was reduced when anterior motion of the knees relative to the toes was restricted via guidewires 16 or altered by manipulating foot position during squatting. 37 A benefit of relying on simple verbal instruction is that this approach can be easily incorporated by exercise professionals who already typically utilize verbal cues to guide exercise technique.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…For both types of verbal instruction (FoAin and FoAex), participants demonstrated a medium or large reduction in PFJFs and PFJS compared with baseline (based on the effect size statistic). These results supplement earlier findings, which indicated that knee loading was reduced when anterior motion of the knees relative to the toes was restricted via guidewires 16 or altered by manipulating foot position during squatting. 37 A benefit of relying on simple verbal instruction is that this approach can be easily incorporated by exercise professionals who already typically utilize verbal cues to guide exercise technique.…”
Section: Discussionsupporting
confidence: 89%
“…[13][14][15] A common belief is that allowing the knees to translate forward in excess during squat performance increases the forces and stress on the knee. Results reported by Kernozek et al 16 appear to support this common belief, as they found that PFJFs and PFJS were greater when young females performed bodyweight squats where their knees were required to move past their toes, compared with squats where their knees needed to remain behind their toes. Guidewires were used to direct/restrict knee motion during the squat trials for both conditions (ie, knees past toes and knees behind toes).…”
mentioning
confidence: 71%
“…However, the PFJRF in this study increased to a larger extent than PF contact area, thereby resulting in greater PFJS. Despite a larger contact area, increased PFJS is typically observed with increased knee flexion during weight bearing activities [27]. Previous work has shown that altering foot strike pattern and also cadence may influence PFJS and PFJRF, respectively [8,16].…”
Section: Discussionmentioning
confidence: 99%
“…In the sagittal plane, forward trunk lean, anterior knee excursion, and ankle dorsiflexion mobility can all impact PFJS. 28,[33][34][35] PFJS can be reduced by increasing forward trunk lean during CKC knee-strengthening exercises. Escamilla et al 34 found that compared with wall squats, ascending from a single-leg squat creates less PFJS from 90 to 60 .…”
Section: Lower-extremity Mechanics In the Cardinal Planesmentioning
confidence: 99%